Nurturing resilience in American Indian/Alaska Native preschool children: the role of cultural socialization, executive function, and neighborhood risk - Merculief, Alexis; Lipscomb, Shannon; McClelland, Megan M.; Geldhof, G. John; Tsethlikai, Monica (Frontiers in Psychology, 2023)
Introduction: American Indian and Alaska Native (AI/AN) children possess numerous cultural assets, yet higher exposures to neighborhood risks (e.g., lack of housing, crime) may present barriers to healthy cognitive development, including executive function (EF). Cultural socialization may promote resilience and support children's early cognition, but this has not been adequately studied. The present study examined the effects of neighborhood risk and cultural socialization on EF for AI/AN preschool children. Method: Parents/caregivers of 768 AI/AN preschoolers from the 2015 AI/AN Head Start Family and Community Experiences (FACES) Study rated neighborhood risk via two scales: "Neighborhood Problems" and "Environmental Conditions," and cultural socialization practices via two scales: cultural activities and tribal language activities. Children's EF was measured directly using the Pencil Tap Task and the Leiter-R attention subscale. Results: Families perceived neighborhood risks as relatively low, and overall risk did not predict children's EF. However, higher average language socialization was significantly related to higher EF, as were two specific language activities (encouraging children to learn their tribal language, making sure children heard their tribal language) and two cultural activities (playing AI/AN games, participating in tribal ceremonies), controlling for neighborhood risk. Discussion: Findings suggest some aspects of cultural socialization may promote resilience among AI/AN preschoolers by supporting early EF. Mechanisms may include increased spiritual, social, and cultural connections, and practice with EF skills during cultural games. Future research should partner with AI/AN communities to investigate culturally grounded EF interventions and reevaluate measures of neighborhood risk to promote resilience and connectedness for AI/AN children.